Factores determinantes de los emprendimientos exitosos en la ciudad de Ambato provincia de Tungurahua en el sector de calzado. - Narváez Jiménez, Carlos Rafael (2018)
The present research project as objetive to establish the factors that affect in the sustainability of the business at the footwer area from Ferrroviario Mall in Ambato city- Tungutahua province.The problem of the footwear business is that they do not achieve to stay in time, that is to say, they can not reach to their first three years of operation. Causing the closure of them. Thus, in the present research it used primary and secondary sources. Also, it did a bibliographic framework of the business stage and the possibles factors that affect. It calculated a sample about 260 business from Ferroviario Mall in Ambato city, the data were obtained fron the Gobierno Autonomo Descentralizado de Ambato (GAD). The methodology used has a quantitative approach, the technique that it applied was the survey throug a questionaire and it obtained information of the following variables: firts it got general information about gender, educational level of the business people, second it got the information about age, experience, the academic training, third stage information about organization as the size, indebtedness and growth , and fourth place it got information about external factors that consisted in increasing information on the growth of the area and the government policies. In conclusión it highlights that the financing and government policies are determinat factors that affect the sustainability of the business from footwear area in Ambato city Tungurahua province.